Enhancing the Performances of Polymeric PVDF Membranes for Oil/Water Separation by Hydrophilic and Underwater Oleophobic Surfaces Modification - Faraziehan Senusi; Benjamin Ballinger; Suzylawati Ismail (Indonesian Journal of Chemistry, 2020)
This paper investigates the permeability and separation performance of polyphenolic-amine coated PVDF membrane with hydrophilic (26.9 ± 5.6°) and underwater oleophobic (162.1 ± 5.1°) surface modification. Surface chemical structures, surface compositions and hydrophilicity of membranes were investigated by Attenuated Total Reflectance Fourier transform infrared (ATR-FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and contact angle analyses, respectively. The separation of emulsion oil solutions was evaluated using cross-flow filtration mode in term of high permeation flux and excellent oil resistance. Then, the flux recovery ratio of filtration process was calculated at different transmembrane pressures (TMP) and initial concentrations of emulsion feed solutions. The results showed a decrease in the flux recovery ratio at higher pressures and initial oil concentrations. By applying Hermia’s blocking model, formation of cake layer shows dominant fouling mechanism for the emulsion oil separation process.